Decision-Making and the Alternative Five Factor Personality Model: Exploring the Role of Personality Traits, Age, Sex and Social Position - Urieta, Patricia; Aluja, Anton; Garcia, Luis F.; Balada, Ferran; Lacomba, Elena (Frontiers in Psychology, 2021)
This study explores the relationship between decision-making style, as measured by the Melbourne Decision Making Questionnaire, and personality based on alternative five-factor model along with effect of age, sex and social position on such styles. A large sample of community and undergraduate students (n= 1,562; Mage=40.03, SD =18.43) was analyzed. The results showed that Neuroticism and Extraversion were significantly related to the non-vigilant styles Hypervigilance, Buck-passing and Procrastination. Women scored significantly lower in Vigilance and higher in Hypervigilance, Buck-passing and Procrastinations than men. Age was significantly related to decision-making style in a U-shaped fashion. The Social Position Index was significantly related to all decision-making styles. The most predictive personality domains regarding decision-making scales were Aggressiveness (negatively) and Activity for Vigilance, and Neuroticism for Hypervigilance, Buck-passing and Procrastination. Age, sex and social position had a small/medium overall effect on the four dimensions of Melbourne Decision Making Questionnaire (p < .001) with a 2 of .038, .068, .050 and .031 for Vigilance, Hypervigilance, Buck-passing and Procrastination, respectively. Based on scores on a single factor dimension of the MDMQ, the profile of participants with higher scores was characterized by lower age, more likely to be females, lower social position, higher levels of Aggressiveness, less Activity, less Extraversion, and higher Neuroticism.